1981
DOI: 10.4138/1372
|View full text |Cite
|
Sign up to set email alerts
|

Flute casts and related structures on moulded silt injection surfaces in continental sandstone of the Boss Point Formation: southeastern New Brunswick, Canada

Abstract: Canada 3 E3L 4L5Flute, load and groove cases occur widely at the sharp Interfaces of slltstone diapirs, injection lenses, and pods In fluvial sandstone of the Boss Point Formation of southeastern New Brunswick.These concordant and discordant injection features range from approximately 20 centimetres (pods) to many metres (injection lenses) in diameter. They are confined to "brecciform intervals" that can be traced along strike and dip for a hundred metres or more.The flute, load and groove casts on the injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Peterson (1968), van de Poll and Patel (1981), van de Poll and Plint (1983), Plint et al (1983), Keighley and Pickerill (1994), and Aalt (1996) reported many ''flow structures,'' especially flute-like or ripple-like marks developed at the interface of injected mud and hosted sand or of injected sand and hosted mud. Unfortunately, no contact plane can be observed in plan view for the SFD layer.…”
Section: Intrastratal Flow and Flow Differentiationmentioning
confidence: 95%
“…Peterson (1968), van de Poll and Patel (1981), van de Poll and Plint (1983), Plint et al (1983), Keighley and Pickerill (1994), and Aalt (1996) reported many ''flow structures,'' especially flute-like or ripple-like marks developed at the interface of injected mud and hosted sand or of injected sand and hosted mud. Unfortunately, no contact plane can be observed in plan view for the SFD layer.…”
Section: Intrastratal Flow and Flow Differentiationmentioning
confidence: 95%
“…Rejection of the previous three hypotheses, as unsatisfactory because they fail to account for all features, leads to Hypothesis 4; that the cavity and the associated structures are not primary but are entirely the result of secondary processes related to diapirrc intrusion. This hypothesis was first suggested by van de Poll & Patel (1981) to account for similar ornamentation on mudstone bodies within brecciforms in the Boss Point Formation, at Alma and Cape Enrage some 45 km southwest of Sackville. Of particular interest within the context of the present discussion are the well-developed, comet-shaped flute moulds on the wall of a large mudstone cavity at Cape Enrage in a brecciform containing mud bodies ranging from a few centimetres to several metres in diameter (van de Poll & Patel, 1981, Figs 9 & lo).…”
Section: Hypothesismentioning
confidence: 86%
“…(4) It is entirely secondary in origin, being due to diapiric intrusion from the mudstone bed below ; the ornamentation was formed by rheoplasis (van de Poll & Patel, 1981), as a result of the actual process of intrusion when both the mud and host sand were in a semi-fluid or liquefied state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The steeply inclined mudstone surfaces were interpreted by these authors as original channel margins, and the detached mudstone masses as slump blocks emplaced into the channels through bank collapse. However, other workers have attributed the structures to 'rheoplasis' (flow-molding), a process of simultaneous loading and differential flow across a sandmud interface during early burial [van de Poll & Patel, 1981, 1989, 1990Keighley & Pickerill, 1994, 1996. The detached mudstone masses have been described as mud diapirs.…”
Section: Introductionmentioning
confidence: 99%